Perbandingan Aktivitas Anti Bakteri Ekstrak Etanol Dan Ekstrak N-Heksana Daun Mangga Arum Manis (Mangifera Indica L. var. arum manis) Terhadap Propionabacterium Acnes - Ratu Mutiara Zakiah; Vida Elsyana; Selvi Marcellia (Jurnal Ilmiah Wahana Pendidikan, 2023)
Acne is a disease caused by chronic inflammation of the pilosebaceous unit caused by bacteria, one of it is Propionibacterium acnes. Acne treatment can be done using nature component, one of it is sweet arum mango leaves. This study aims to identify which mango leaf extract has a minimum inhibitory power (MIC) which is more effective. The extraction carried out in this study was percolation with 96% ethanol and n-hexane as solvents. The extraction yield of 96% ethanol extract was 3.5%, while the n-hexane extract yielded 2.5%. The MIC results from the inhibitory power test with concentrations of 1%, 3%, 5%, 7%, and 9%, the 96% ethanol extract with a concentration of 1% obtained a value of 2.1 mm, while the n-hexane extract has an inhibitory power starting from a concentration of 5% with an average diameter of 1.26 mm. It can be concluded that the arum manis mango leaf extract (Mangifera indica L. var. arum manis) has an inhibitory effect on the growth of Propionibacterium acnes bacteria and the ethanol extract of arum manis mango leaf has more effective antibacterial activity than the n-hexane extract of arum manis mango leaves